Sierpień 1980 - zaskoczenie czy spodziewany wybuch? Konflikt społeczno-polityczny w Polsce w ocenach dziennikarzy zachodnioniemieckich = August 1980 - a surprise or an expected outburst? The socio-political conflict in Poland as viewed by the West-German journalists - Świder, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
When the first reports concerning the protests and strikes caused by the price increase emergedat the beginning of July 1980, the West-German journalists immediately recalled the protestswhich sparked off in Poland in 1970 and 1976. While anticipating further complications ofpolitical and economic situation, the development of the circumstances and the necessity ofeconomical reforms were being debated.
Keywords: czasopisma niemieckie; Solidarność; Polska - historia; 20 w.